Executions of Fiduciaryry Guarantee Post Constitutional Court Decision No. Nomor: 18/Puu-Xvii/2019 - Nowinri Hilgutshiany Marini Pratiwi Pitanuki (Fakultas Hukum Universitas Lampung, 2020)
The background that underlies the conduct of this legal research is the existence of a conflict of norms, namely in the Fiduciary Guarantee Act, direct execution can be carried out if the debtor has committed an injury (also called default), but in the Constitutional Court ruling Number: 18 / PUU-XVII / 2019 This is done immediately after the debtor is injured but requires a statement of voluntary interest from the debtor or through a judicial decision. The problem in this research is related to the essence of the execution of fiduciary guarantees, the development of the fiduciary guarantee execution arrangements before and after the Constitutional Court decision Number: 18 / PUU-XVII / 2019 the implications of the Constitutional Court decision Number: 18 / PUU-XVII / 2019 on the principles of simple, fast, and low cost. The type of research used in this research is juridical normative, using a statutory approach and a case approach, as well as primary and secondary legal materials which are analyzed by grammatical and systematic interpretation. The results of this study indicate that the essence of the execution of fiduciary guarantees is to sell fiduciary collateral as repayment of debtor's unfulfilled obligations. The creditor has the right to collect the debtor's achievements including to collect all instalments and other fees that have not been paid by the debtor, and has the right to execute the object that is used as collateral without having to return the excess price from the sale of the object. The execution of the fiduciary guarantee prior to the enactment of the Constitutional Court Decision Number 18 / PUU-XVII / 2019 is based on the Fiduciary Guarantee Certificate which contains the words